High-speed electro-optic modulator with group velocity matching on silicon substrate - Liu, Yingbo; Li, Haiou; Li, Yue; Li, Haisheng; Hao, Yuxiang; Qin, Liangpeng; Yang, Jiayu (Frontiers in Bioengineering and Biotechnology, 2025)
Electro-optic modulators with low driving voltage and wide bandwidth are critical for advanced analog and digital communication systems. To achieve high-speed thin-film lithium niobate (TFLN) electro-optic modulators on silicon substrates, this work proposes a hybrid-loaded T type-U type traveling-wave electrode structure (TU-TWEs). The core of TU-TWEs in the introduction of an inductance compensation mechanism, which can effectively reduce the microwave refractive index and weaken the “slow light” effect, thereby matching the group velocity of light with the microwave velocity. We demonstrate a high-speed TFLN electro-optic modulator on a silicon substrate, with an electro-optic bandwidth greater than 110 GHz and a half-wave voltage of 1.35 V.